Changes in Gray cast iron over the last century-An initial study - Shivarudrappa,Puneeth Kumar (2021)
This thesis report summarizes the research on the cold aging of gray cast iron samples dating back 100 years, and how researchers looked at the phase history and amount of impurities and trace metals generated by recycling. Initially, the topic of the thesis is introduced, with an explanation and general information on gray cast iron. The chemistry and structure of gray cast iron are both discussed. The impact of the various elements in the composition is briefly described. Then, the concept of aging has been explained also the influence of carbides, oxides and nitrides with aging is described. Gray cast iron has excellent machinability due to the inclusion of almost constant graphite flakes in the microstructure. Moving forward, the methods like x- ray fluorescence, Vickers hardness, and optical microscope with the Alicona Infinite 3D microscope are used for analysis are explained one by one. In methodology section, the detailed explanation of sample preparation and the required procedure for preparation is discussed. The data obtained from the various experiments are collected and analyzed. We obtained data from x- ray fluorescence as it shows the percentage of concentration of different materials in the gray cast iron. By the aid of Vickers hardness, we got the hardness value of each sample at different load. With the help of optical microscope, we are able to get the images of graphite structure of GCI at different magnifications. Finally, the analysis is done by the data what we got from various methods.
Keywords: Gray cast iron; age strengthening; and machinability.